Comparative Research on the Zahir and Batin Thought - Mahgoub El-Tigani Mahmoud (European Scientific Journal, ESJ, 2016)
This research paper makes an attempt to expound the Muslim concepts of al-zahir [the evident] and the al-batin [the intrinsic] which touch deeply upon both spiritual and secular practices to ascertain possible similarities and differences between the Muslim and the non-Muslim realms. Despite centuries of economic and cultural relationships, recent times have been loaded with political and media stereotyping of Islam as a “warring” religion whose militants “threaten” the regional peace and international order. Almost nothing is mentioned about the “intrinsic” motives that underlie “evident” dictions of all parties of the conflict. To establish corrective understanding between the Muslims and the non-Muslims as a unified human family, comparative research is critically needed to educate and to disseminate the facts about Islam and the Muslim heritage to expand the peaceful co-existence and the full enjoyment of freedoms and human rights to all humans. In this context, the paper analyzes key concepts of the al-zahir and al-batin to appreciate the meanings of the Muslim Truth and the Hikmat al-Ta’aruf teachings, in comparison with non-Muslim beliefs and secular thought. To conclude, systematic research is crucial to help reconcile the parties by the establishment of comparable ontologies for the Muslim and non-Muslim thought.